A FHIR Human Leukocyte Antigen (HLA) Interface for Platelet Transfusion Support - Gordon, William J; Baronas, Jane; Lane, William J (Applied Clinical Informatics, 2017)
Platelet transfusions are a cornerstone of therapy for patients who develop thrombocytopenia while undergoing Hematopoietic Stem Cell Transplantation (HSCT). Many patients who develop Platelet Transfusion Refractoriness (PTR) require HLA-matched platelets. Identifying these patients early could lead to better utilization of platelets as well as increased platelet counts. We built a SMART on FHIR visualization tool to aid the oncology, blood bank, and blood donor center teams in identifying these patients by showing trends in thrombocytopenia along with a computer generated calculated Panel Reactive Antibody (cPRA) level. To do this, we required a FHIR interface to our HLA database. We describe our methods and outcome for constructing this FHIR interface, as well as the architecture and data flow of HLA data from its proprietary database to the SMART on FHIR environment and application database along with RESTful cPRA web service calculator. Future work will evaluate the clinical impact of this platelet visualization tool and overall success of our FHIR implementation.Citation: Gordon WJ, Baronas J, Lane WJ. A FHIR human leukocyte antigen (HLA) interface for platelet transfusion Support. Appl Clin Inform 2017; 8: 603–611 https://doi.org/10.4338/ACI-2017-01-CR-0010
Keywords: Laboratory information systems; standards; FHIR; HLA antigens; platelet transfusion